Boy : tales of childhood - Dahl, Roald (London : Puffin, 1986)
Presents humorous anecdotes from the author's childhood, including his education at an English boarding school and summer vacations in Norway.
"First published in Great Britain by Jonathan Cape Ltd., 1984"--T.p. verso.
"First published in the United States of America by Farrar, Strauss & Giroux, 1984"--T.p. verso.
6.4
5-8.
5-8
Keywords: Dahl, Roald -- Juvenile literature; Dahl, Roald; Dahl, Roald; Authors, English -- 20th century -- Biography -- Juvenile literature; Authors, English; English authors -- Biography